Intoxication : An Ethnography of Effervescent Revelry - Tutenges, Sebastien (Book collections on Project MUSE., 2023)
"For two decades, Sebastien Tutenges has conducted research in bars, nightclubs, festivals, drug dens, nightlife resorts, and underground dance parties in a quest to answer a fundamental question: Why do people across cultures gather regularly to intoxicate themselves? Vivid and at times deeply personal, this book offers new insights into a wide variety of intoxicating experiences, from the intimate feeling of connection among concertgoers to the adrenaline-fueled rush of a fight, to the thrill of jumping off a balcony into a swimming pool. Tutenges shows what it means and feels to move beyond the ordinary into altered states in which the transgressive, spectacular, and unexpected takes place. He argues that the primary aim of group intoxication is the religious experience that Émile Durkheim calls collective effervescence, the essence of which is a sense of connecting with other people and being part of a larger whole. This experience is empowering and emboldening and may lead to crime and deviance, but it is at the same time vital to our humanity because it strengthens social bonds and solidarity. The book fills important gaps in Durkheim's social theory and contributes to current debates in micro-sociology as well as cultural criminology and cultural sociology. Here, for the first time, readers will discover a detailed account of collective effervescence in contemporary society that includes: an explanation of what collective effervescence is; a description of the conditions that generate collective effervescence; a typology of the varieties of collective effervescence; a discussion of how collective effervescence manifests in the realm of nightlife, politics, sports, and religion; and an analysis of how commercial forces amplify and capitalize on the universal human need for intoxication"--